Correlation of p53 Expression with Grade and Stage of Ovarian Surface Epithelial Cancer - Hossain, Md Sazzad; Kamal, Md; Syeda Noorjahan Karim; Nowsher, Md Neaz; Mehdi Ashik Chowdhury; Nurjahan Nishat (Mediscope, 2023)
Introduction: Advanced ovarian cancer is characterized by a poor prognosis and the development of resistance to chemotherapy. In the absence of definite etiologic factors and effective tools for screening, the only possible means of improving survival would be to develop effective targeted therapy. Expression of p53 in ovarian cancer may serve as a promising therapeutic strategy to treat, prevent visceral metastasis and relapse. Objective: The study was carried out to find out the correlation of p53 expression with the grade and stage of ovarian cancers. Methods: The study had 45 cases. These cases were previously reported as ovarian surface epithelial cancers. Grading was done in all cases. Pathological staging of tumour (pT) was done in 30 cases and pathological staging of lymph node metastasis (pN) was done in 10 cases. Distant metastasis was present in only 1 case. Result: p53 immunostaining was found positively correlated & associated with the grade & stage of ovarian surface epithelial cancers. Conclusion: p53 expression may be important for prognostic outcomes or useful targets of therapeutic intervention. Mediscope 2023;10(2): 42-49